Benefiting All Users: Gender Equality and Inclusion - Gumucio, Tatiana; Blumenstock, Ali; Lewis, Amanda; Bradley-Cook, Julia; Apotsos, Alex (Climate Links, 2020)
Women’s needs and priorities often differ from those of men, and their ability to access and use climate services is significantly more constrained. To address these disparities, and to ensure access to and benefit from these services, it is critical to use gender-informed approaches.